Intranasal neuropeptide Y is most effective in some aspects of acute stress compared to melatonin, oxytocin and orexin - Zubkov, Eugene; Abramova, Olga; Zorkina, Yana; Ochneva, Aleksandra; Ushakova, Valeria; Morozova, Anna; Gurina, Olga; Majouga, Alexander; Chekhonin, Vladimir (Frontiers in Pharmacology, 2022)
Objectives: In the current study, we compared the effects of a single intranasal administration of clomipramine with effects of four neuropeptides, melatonin, oxytocin, orexin, and neuropeptide Y, to compare them in an acute stress model. Methods: The anti-stress effect was evaluated in the sucrose preference and forced swimming tests. Serum corticosterone level in rats was measured to evaluate the stress response. Results: Neuropeptide Y reduced immobilization time in the Porsolt test and decreased corticosterone levels, but increased the anhedonia. Orexin had no positive effect on animal behavior, but decreased corticosterone levels. Oxytocin decreased immobilization time, maintained anhedonia at the level of control, but did not affect corticosterone levels. Melatonin demonstrated no positive effects in any of the tests. Conclusion: The intranasal administered neuropeptide Y could be a promising compound for the treatment of stress disorders.